hMEF2C gene encodes skeletal muscle- and brain-specific transcription factors. - McDermott, J C (1993)
The myocyte enhancer-binding factor 2 (MEF2) site is an essential element of many muscle-specific enhancers and promoters that binds nuclear proteins from muscle and brain. Recently, we have cloned a family of MEF2 transcription factors produced by two genes that, at the mRNA level, are broadly expressed and produce tissue-specific isoforms by posttranscriptional processes (Y.-T. Yu, R. E. Breitbart, L. B. Smoot, Y. Lee, V. Mahdavi, and B. Nadal-Ginard, Genes Dev. 6:1783-1798, 1992). Here, we report the isolation and functional characterization of cDNA clones encoding four MEF2 factors derived from a separate gene that we have named hMEF2C. In contrast to those of the previously reported genes, the transcripts of the hMEF2C gene are restricted to skeletal muscle and brain. One of the alternate exons is exclusively present in brain transcripts. The products of this gene have DNA-binding and trans-activating activities indistinguishable from those of the previously reported MEF2 factors. The hMEF2C gene is induced late during myogenic differentiation, and its expression is limited to a subset of cortical neurons. The potential targets for this transcription factor in a subset of neurons are not known at this time. The strict tissue-specific pattern of expression of hMEF2C in comparison with the more ubiquitous expression of other MEF2 genes suggests a different mode of regulation and a potentially important role of hMEF2C factors in myogenesis and neurogenesis.